Battery related cobalt and REE flows in WEEE treatment. (November 2015) - Sommer, P.; Rotter, V.S.; Ueberschaar, M.
Highlights: Resource potential of WEEE batteries lost due to non-collection. WEEE batteries have high relevance for cobalt recycling. Rare earth elements are presently not recycled from NiMH batteries due to economic barriers. Battery chemistry specific sorting will enable future recycling. Abstract: In batteries associated with waste electrical and electronic equipment (WEEE), battery systems can be found with a higher content of valuable and critical raw materials like cobalt and rare earth elements (REE) relative to the general mix of portable batteries. Based on a material flow model, this study estimates the flows of REE and cobalt associated to WEEE and the fate of these metals in the end-of-life systems. In 2011, approximately 40 Mg REE and 325 Mg cobalt were disposed of with WEEE-batteries. The end-of-life recycling rate for cobalt was 14%, for REE 0%. The volume of waste batteries can be expected to grow, but variation in the battery composition makes it difficult to forecast the future secondary raw material potential. Nevertheless, product specific treatment strategies ought to be implemented throughout the stages of the value chain.